Racial differences in nocturnal dipping status in diabetic kidney disease: Results from the STOP‐DKD (Simultaneous Risk Factor Control Using Telehealth to Slow Progression of Diabetic Kidney Disease) study. Issue 12 (20th August 2017) - Zullig, Leah L.; Diamantidis, Clarissa J.; Bosworth, Hayden B.; Bhapkar, Manjushri V.; Barnhart, Huiman; Oakes, Megan M.; Pendergast, Jane F.; Miller, Julie J.; Patel, Uptal D.
Abstract : While racial variation in ambulatory blood pressure (BP) is known, patterns of diurnal dipping in the context of diabetic kidney disease have not been well defined. The authors sought to determine the association of race with nocturnal dipping status among participants with diabetic kidney disease enrolled in the STOP‐DKD (Simultaneous Risk Factor Control Using Telehealth to Slow Progression of Diabetic Kidney Disease) trial. The primary outcome was nocturnal dipping—percent decrease in average systolic BP from wake to sleep—with categories defined as reverse dippers (decrease <0%), nondippers (0%–<10%), and dippers (≥10%). Twenty‐four‐hour ambulatory BP monitoring was completed by 108 participants (54% were nondippers, 24% were dippers, and 22% were reverse dippers). In adjusted models, the common odds of reverse dippers vs nondippers/dippers and reverse dippers/nondippers vs dippers was 2.6 (95% confidence interval, 1.2–5.8) times higher in blacks than in whites. Without ambulatory BP monitoring data, interventions that target BP in black patients may be unable to improve outcomes in this high‐risk group.